Kręte drogi odchodzenia od przestępczości - Muskała, Maciej (Studia Edukacyjne, 2022)
Moving away from crime does not always proceed along a straight path. Many offenders abandon their criminal behavior to return to it again after some time, although not always with the same intensity and frequency. Therefore, the process of rehabilitation, the specific process of abandoning a life of crime, must be seen as a long-term and dynamic process. It is characterised by numerous relapses to the “old” criminal style of operation, to a greater or lesser extent depending on the individual himself. These relapses do not occur due to single causes, but are influenced by a variety of coexisting factors. The aim of this paper is to present and analyse the Self-Regulatory Model of Relapse Prevention (in its modified SRM-R version), strongly inspired by the Good Lives Model, which illustrates possible ways away from delinquency not always in a linear way, but precisely through a variety of pathways.